Effectiveness of Items of Jarak Leaf Extract (Jatropha Curcas) with Different Dosages to Prevent Attacks of Fungs Saprolegnia sp on Gold Fish (Cyprinus carpio L) EGGS - Juharni, Juharni; Abdullah, N.; Arisona, Y. (Agrikan Jurnal Agribisnis Perikanan, 2023)
The aim of the study was to determine the effect and optimal dose on hatchability, hatching time and prevalence. The study was carried out in two stages, namely the manufacture of jatropha leaf simplicia dried using an oven at 70 oC for 5 minutes. Puree using a blender. Weighed according to the treatment, namely A 3 g/L, B 5 g/L, C 7 g/L and D 0 g/L. The next stage is spawning the broodstock, and selecting 2,400 eggs that have been successfully fertilized, each treatment with 200 eggs. Each treatment was soaked for 4 minutes. The eggs were transferred to a hatching container with a volume of 5 L of water. The experiment was conducted using an experimental method (CRD), the factor tested was the effectiveness of castor leaf extract with different doses on hatching time, hatchability and prevalence. The results of observations of hatching times have a different number of hatchings. Treatment 3g/L 5 grains, treatment 5g/L 3 grains, without soaking 1 grain with hatching time 30 hours after fertilization. The most eggs hatched at 42-54 hours in the 3g/L treatment 479 eggs and the lowest in the treatment without soaking 258 eggs. For treatment 5g/L 419 grains and treatment 7g/L 380 grains. The effectiveness of giving effect, prevalence and presentation of hatching eggs in the 3g/L treatment has a success rate of 5%, for hatching time of 30-52 hours, prevalence is 20.17% and percentage of hatching eggs is 79.83%.